Mining Transformation Towards a Green Economy : A Normative Analysis of the Legal and Environmental Governance Framework in Indonesia - Mas Subagyo Eko Prasetyo; Giyarni; Cut Fitriyani Meilita; Mas Rara Tri Retno Heryani; Alwan Hadiyanto; Linayati Lestari (Vifada Assumption Journal of Law, 2026)
Purpose: Indonesia’s mining sector holds a strategic position in national development and the energy transition, but it also generates significant ecological and social pressures. This study examines how mining can be repositioned as an instrument of the green economy through the strengthening of legal norms and environmental governance in Indonesia. Research Design and Methodology: This study employs normative legal research using statute, conceptual, and limited comparative approaches. The legal materials consist of legislation on mineral and coal mining, environmental protection and management, reclamation and post-mining obligations, low-carbon development policies, and scientific literature on the green economy, sustainable mining, and natural resource governance. These materials are analysed through qualitative normative analysis. Findings and Discussion: The study finds that Indonesian law provides a normative basis for integrating sustainable development, environmental protection, social justice, reclamation, and public participation into mining governance. However, its implementation remains constrained by regulatory fragmentation, institutional overlap, weak enforcement, limited incentives, and unequal community protection. The article argues that green mining governance requires legal strengthening, institutional harmonization, technological innovation, economic incentives, and collaborative accountability involving the state, business actors, local communities, and epistemic communities. Implications: As a normative framework for green mining governance in Indonesia, this study connects its findings with practical contributions for policymakers, regulatory agencies, and law enforcement agencies. The study integrates mining law, environmental governance, sustainable development, and community protection as a basis for more responsible natural resource policies and future legal reforms in the mining sector.